Characterization of Fatty Acid Composition Underlying Hypothalamic Inflammation in Aged Mice - Kim, Ye Jin (Molecules, 2020)
Degenerative diseases, which can develop during aging, are underlined by inflammatory processes. Hypothalamic inflammation triggered by elevation in circulating fatty acid levels is directly coupled to metabolic disorders. The present study aimed to investigate and characterize the hypothalamic inflammation and composition of fatty acids in the hypothalami of aged mice. We verified that inflammation and microglial activation occur in the hypothalami of aged mice by performing quantitative real-time PCR and using immunohistochemistry methods. In addition, we observed increased levels of various saturated fatty acids in the hypothalami of aged mice, whereas no major changes in the levels of circulating fatty acids were detected using gas chromatography with a flame ionization detector. Collectively, our current findings suggest that increases in saturated fatty acid levels are coupled to hypothalamic inflammation and thereby cause perturbations in energy metabolism during the aging process.